University graduates in metropolitan and peripheral areas: mobility, occupational choice and outcomes. Issue 6 (3rd June 2022) - Drejer, Ina; Holm, Jacob Rubæk; Nielsen, Kristian
ABSTRACT: This study explores the relationship between mobility patterns, occupational choices and performance outcomes of university graduates from metropolitan and peripheral areas. After statistical matching, we find opposite outcomes for geographically mobile wage earners and entrepreneurs. Graduates from the periphery who stay in the study region to work have an inferior performance outcome compared with those who move to the metropolitan region. This 'penalty' is not present for non-movers in metropolitan areas. Non-mobile entrepreneurs benefit from attachment to their home region, in particular in the periphery. These findings can help direct regional policy aimed at retaining graduates and promoting regional development.